## Solving the Equation (x+2)(x+9)(x-1) = 0

This equation represents a cubic polynomial set equal to zero. To find the solutions (also called roots or zeros), we use the **Zero Product Property**:

**If the product of multiple factors equals zero, then at least one of those factors must equal zero.**

Applying this to our equation:

(x+2)(x+9)(x-1) = 0

We need to find the values of x that make each factor equal to zero:

**x + 2 = 0**=> x = -2**x + 9 = 0**=> x = -9**x - 1 = 0**=> x = 1

Therefore, the solutions to the equation (x+2)(x+9)(x-1) = 0 are:

**x = -2, x = -9, and x = 1**

**Graphical Interpretation**

These solutions represent the x-intercepts of the graph of the cubic function y = (x+2)(x+9)(x-1). The graph will cross the x-axis at these three points.

**In summary, the equation (x+2)(x+9)(x-1) = 0 has three solutions: -2, -9, and 1.**